Mutation spoT of Escherichia coli increases expression of the histidine operon deleted for the attenuator. - Winkler, M E (1979)
F'-episomes carrying the Salmonella typhimurium wild-type or attenuator-deleted histidine (his) operons were introduced into Escherichia coli strains containing relA or spoT single and double mutations known to affect guanosine 3'-diphosphate 5'-diphosphate (ppGpp) and guanosine 3'-triphosphate 5'-diphosphate (pppGpp) levels. Expression of the his operon and expression of the gene for 6-phosphogluconate dehydrogenase (gnd) were measured during balanced growth in amino acid-rich and minimal media. The data were consistent with the interpretation that ppGpp is a positive effector of his operon expression, whereas pppGpp is not an essential effector. The conclusion that his operon expression is maximally stimulated at a lower than maximum intracellular ppGpp concentration was further confirmed. Neither ppGpp nor pppGpp appeared to influence gnd gene expression. The metabolic regulation of the E. coli his operon was found to be similar to the ppGpp-meidated metabolic regulation of the S. typhimurium his operon.